2022
DOI: 10.1098/rsos.211781
|View full text |Cite
|
Sign up to set email alerts
|

Neophobia and innovation in Critically Endangered Bali myna, Leucopsar rothschildi

Abstract: Behavioural flexibility can impact on adaptability and survival, particularly in today's changing world, and encompasses associated components like neophobia, e.g. responses to novelty, and innovation, e.g. problem-solving. Bali myna ( Leucopsar rothschildi ) are a Critically Endangered endemic species, which are a focus of active conservation efforts, including reintroductions. Gathering behavioural data can aid in improving and developing conservation strategies, like pre-release trai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…having less neofobia) (e.g. Martínez‐Abraín et al, 2022; Miller et al, 2022). Birds with a stable trend but a previous wintering status showed a relatively high probability of colonising, which indicates that wintering status (prior information availability) may be the main driver of colonisation.…”
Section: Discussionmentioning
confidence: 99%
“…having less neofobia) (e.g. Martínez‐Abraín et al, 2022; Miller et al, 2022). Birds with a stable trend but a previous wintering status showed a relatively high probability of colonising, which indicates that wintering status (prior information availability) may be the main driver of colonisation.…”
Section: Discussionmentioning
confidence: 99%
“…We can only speculate about the nature of the mechanisms involved. Several studies have shown that juveniles are often more explorative and neophilic than adults [134][135][136][137][138][139][140]. Hence, the seasonal difference in neophilia and social learning abilities may be related to the prevalence of younger octopuses during spring-summer.…”
Section: Discussionmentioning
confidence: 99%
“…But this pattern is far from universal (see reviews: Griffin 2022 ; Inzani et al 2023 ). For example, in corvids it has been reported that the neophilia of urban birds is higher only in certain circumstances, due to experience with specific items (like litter) or even specific humans ( Echeverría and Vassallo 2008 ; Greggor et al 2016 ; Tryjanowski et al 2016 ; Jarjour et al 2020 ; Miller et al 2022 ). These results suggest that urban areas in general can influence neophilia levels and animals can become accustomed to anthropogenic “novelty.” Therefore, we must be careful in interpreting what is perceived as novel for the populations and individual animals residing within an urban habitat and start to disentangle general neophilia (attraction to novelty) from “anthrophilia.” Here, we suggest the terminology “anthrophobia/ anthrophilia” to distinguish responses directed towards items/ foods that are associated with humans and/ or human habitats.…”
mentioning
confidence: 99%